Patrones de cambios cromáticos en juveniles y adultos de la castañeta Nexilosus latifrons (Cichliformes: Pomacentridae) - Méndez-Abarca, Felipe; Pepe-Victoriano, Renzo; Mundaca, Enrique A. (Revista de Biología Marina y Oceanografía, 2023)
Patterns of temporal chromatic and shape variations of live specimens of Nexilosus latifrons were studied. Observations were made on specimens captured in intertidal pools in the coastal area of Arica, northern Chile, which were kept in captivity for 16 months. Five developmental stages, in which there were noticeable changes in shape and colouration, were described. Findings obtained primarily to improve species identification are discussed, as well as to prevent removal of juvenile specimens from the environment and improve captive breeding practices.